Electrochemistry, Nanomaterials, and Nanostructures - Bueno, Paulo Roberto [UNESP]; Gabrielli, Claude; Leite, E. R. (Springer, 2009)
This chapter deals with the development of new methods for the design of more efficient electrochemical cells destined specifically for energy conversion and storage based on synthesis and design of functional electrodes and electrolytes. The main focus of this chapter is on novel strategies that exploit nanoscale architectures to enhance the efficiency of alternative energy conversion and storage devices as well as on the basic principles of electrochemistry governing the effects of nanoscale design on electrodes and electrolytes. In addition, the chapter provides a review of fundamental electron transfer concepts of relevance to electrochemistry in general and alternative energy devices in particular.